Implementation of E-Filing for Individual Taxpayers at KPP Pratama Medan Timur - Miftha Rizkina; Nur Aliah; Sumardi Adiman (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to see how the Implementation of E-Filing for Individual Taxpayers at the East Medan Primary Tax Service Office. This research uses a qualitative approach with an Analytical Descriptive research method. Data collection techniques in this study consisted of documentation studies and interviews. The results of this study indicate that the implementation of E-Filing for Individual Taxpayers at the KPP Pratama Medan Timur is in accordance with the provisions of tax administration and tax laws and regulations and is almost optimal, although there are still those who choose to report SPT directly to the KPP, but the purpose of using E-Filing which can facilitate taxpayers in fulfilling their tax obligations has been achieved even though it has not been maximized.